2013
DOI: 10.1021/nl402803h
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Deep Traps in Nanocrystal Solids, Their Electronic Properties, and Their Influence on Device Behavior

Abstract: We implement three complementary techniques to quantify the number, energy, and electronic properties of trap states in nanocrystal (NC)-based devices. We demonstrate that, for a given technique, the ability to observe traps depends on the Fermi level position, highlighting the importance of a multitechnique approach that probes trap coupling to both the conduction and the valence bands. We then apply our protocol for characterizing traps to quantitatively explain the measured performances of PbS NC-based sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
144
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(166 citation statements)
references
References 24 publications
(49 reference statements)
14
144
1
Order By: Relevance
“…Our results and other recent publications on the subject yielding similar values 36,37 indicate that while the mobility was comparable in the two material classes, the trap density differed by a factor of three. This motivated us to undertake a closer inspection of these trap densities and their connection to diffusion lengths and transport in CQD solids.…”
Section: Resultssupporting
confidence: 87%
“…Our results and other recent publications on the subject yielding similar values 36,37 indicate that while the mobility was comparable in the two material classes, the trap density differed by a factor of three. This motivated us to undertake a closer inspection of these trap densities and their connection to diffusion lengths and transport in CQD solids.…”
Section: Resultssupporting
confidence: 87%
“…The observation of two distinct distributions may explain why some groups reported states close to the valence level and others associated them with the conduction level. [9][10][11][12][13][14]28] The surface chemistry of PbS CQDs is more complex than simple schemes such as the one in Figure 1a suggest. Even assynthesized CQDs do not only exhibit two differently polarized crystal facets ((001) and (111)), but are also covered with hydroxyl and oleate ions additional to oleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…These classes of materials are level for EDT capped PbS was reported for electron transport experiments. [13,14] For PbS treated with tetrabutylammonium iodide (TBAI) a trap distribution with an activation energy of 0.34 eV was found via temperature-dependent impedance spectroscopy. [15] Using optical pump-probe spectroscopy, the groups of Asbury and Sargent observed a broad photoinduced absorption (PIA) around 0.3 eV with a long lifetime (still visible after 200 µs) for a range of ligands, including EDT and MPA, and attributed this observation to surface trap states.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of a trapped carrier can be estimated using a thermal velocity ~10 6 cm sec -1 and average density of traps N ~10 14 cm -3 for PbS NCs as reported in literature. [30][31][32] It has been found that for ligand exchanged PbS NCs the electron capture coefficient ( ) is ~400 times greater than the hole capture coefficient, therefore electrons are more likely to be trapped. 33 Consequently the electron contribution to the photocurrent is small and the photoconductivity is predominantly due to holes.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%
“…The current focus of much research remains in deep understanding of trap associated charge transport behaviour in PbS NCs and their role in influencing the device performance. [30][31][32][33]45,46 As the gain is principally achieved via a prolonged carrier lifetime this limits the temporal response of the device that requires a fast recombination and subsequent collection of charge carriers. This sets up a fundamental trade-off between photoconductor gain and the bandwidth.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%